Adopsi Anak Dalam Perspektif Al-Qur’an Surah Al-Ahzab Ayat 5: (Kajian Tafsir Maqashidi) - Fithrotin Fithrotin; Lubabah Diyanah; Wakhidatun Nihlah (Program Studi Ilmu Al Quran dan Tafsir Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2023)
This article aims to find out the problems in the implementation of the adoption of children in terms of Islamic law contained in QS. al-Ahzab verses 5. Feeling a child who is not his biological child is often understood as permissible, this is evidenced by the fact that there are still many adoptive parents who entrust their adopted children to him. This study uses the maqashidi interpretation approach to capture the maqashid that exists in the law of child adoption. The result of this work explains that in QS. al-Ahzab verses 5 explains the monasticity of a person to call an adopted son to one other than his father. However, it is allowed if it is because of someone's ignorance. Adoption has been practiced by the Prophet Muhammad since before the prophethood, the Prophet Muhammad adopted Zaid bin Haritsah as his own son.